Telaah Kritis Otonomi Daerah di Indonesia - Auri Adham Putro (Magister Ilmu Administrasi Publik, 2000)
The regional autonomy policy based on Law No. 22/1999 and Law No. 25/1999 is intended to cope with problems of national disintegration of Indonesia. However, during the implementation of this policy, several constraints appear. The first is economic constraint, and the second is political constraint. Economic constraints relates to the shift of local government paradigm from effectiveness and efficiency oriented policy to economic oriented policy, implying also to natural resources exploitation and to decrease of public services. Political constraint is due to excessive political powers of legislatives that are not supported by adequate human resources quality. This will lead to legislative authoritarianism, Therefore, the success of regional autonomy policy depends on the democratic central government that support law enforcement.